Theory of Filipino Substance Use Recovery (SUR): A Grounded Theory Approach - Karen Policarpio Sol; Jemerson Naceno Dominguez (PSIKODIMENSIA, 2021)
Abstract: Treatment for Substance Use Disorder (SUD) is often theory-based however, recovery has not been guided by a theory. This grounded theory study intended to identify how an  individual  maintains  recovery  from  SUD.  Twenty  (20)  recovering  persons  as  the participants in a one-on-one in-depth interview employing Charmaz’s grounded theory methodology  of  analyzing  data,  a  theory  was  developed.  The  theory  of  Filipino Substance  Use  Recovery  (SUR)  generated  five  theoretical  phases:  Exhaustion, Recognition,  Acceptance,  Involvement,  and  Maintenance.  Under  the  Maintenance phase,  components  in  maintaining  a  lifelong  recovery  were  also  identified  such  as autonomy, maturity, support system, positive feelings, and restitution. Furthermore, it recognized  two  recovery  barriers  (internal  and  external  barriers)  thus  explained  the phenomena  of  substance  use  relapse.  In  conclusion,  the  theoretical  foundation  of Filipino SUR could help improve the current treatment and management of SUD in the Philippines.  Findings  could  be  utilized  in  developing  programs  grounded  and contextualized in the Philippine setting to address issues in substance use prevention, harm reduction, intervention, and recovery.  Keywords: Substance Use Disorder (SUD), recovery, relapse, grounded theory